TRANSFORMASI PENDIDIKAN AGAMA ISLAM DALAM KONTEKS SEJARAH SOSIAL DAN PERADABAN ISLAM MELAYU - Novrian Eka Safutra; Lailatul Mukjizat; Maryamah; Zulhijra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to deeply examine the transformation of Islamic Religious Education within the social history and civilizational landscape of Malay Islam, while simultaneously exploring the determinants and challenges that accompany its movement over time. Within this framework, Islamic Religious Education is no longer understood merely as a space for the transmission of normative religious knowledge, but rather as a space for the formation of meaning where values, manners, and spiritual awareness are nurtured and cultivated amidst the increasingly complex currents of change. This research uses a qualitative approach through library research, by examining various relevant academic literature sources. The results of the study indicate that the transformation of Islamic Religious Education has taken place in an evolutionary manner, starting from the intimate traditions of surau, langgar, and pesantren (Islamic boarding schools) centered on teacher-student relationships within the halaqoh circle, moving towards a modern madrasah system that integrates religious knowledge and general knowledge more systematically. These changes did not occur in a vacuum, but were shaped by the dynamics of colonialism, the rise of Islamic renewal, developments in educational policy, and the acceleration of science and technology. However, amidst these transformation efforts, Islamic Religious Education (PAI) also faces significant challenges, ranging from limited digital literacy among educators, infrastructure gaps, and even a moral crisis that is slowly eroding the generation's sense of civility. Therefore, the transformation of Islamic Religious Education (PAI) demands an effort that is not only adaptive and contextual, but also reflective and rooted, so that it does not simply change with the times but remains able to maintain the spirit of Islamic values ​​while guiding civilization toward a more civilized future.